Overlooked Parrot Seed Dispersal in Australia and South America: Insights on the Evolution of Dispersal Syndromes and Seed Size in Araucaria Trees - Tella, José L.; Blanco, Guillermo; Dénes, Francisco V.; Hiraldo, Fernando (Frontiers in Ecology and Evolution, 2019)
While Psittaciformes (parrots and allies) are well recognized as highly-mobile seed predators, their role as seed dispersers has been overlooked until very recently. It remains to be determined whether this role is anecdotic or is a key mutualism for some plant species. We recently found that the large nut-like seeds of the two South American Araucaria tree species (A. araucana in Andean forests and A. angustifolia in Atlantic forests, weighing c. 3.5 and 7g, respectively) are frequently dispersed, and to long distances, by parrots. Moreover, both observational and experimental work demonstrated that dispersed seeds can germinate faster after partial predation by parrots. Here, we hypothesized that a third, even larger-seeded (17.5g) congeneric Australian species (A. bidwillii) is also dispersed by parrots. We surveyed 52 A. bidwillii and 42 A. cunninghamii (a sympatric species with small winged seeds, c. 0.2g) during the seeding period. We found that sulphur-crested cockatoos (Cacatua galerita) consumed large amounts of seeds from all of the A. bidwillii trees surveyed. Cockatoos dispersed ca. 30% of the seeds they removed from the mother tree, carrying the seeds to distant perches for handling or dropped them while flying. Dispersal distances ranged between 10 and 153 m (mean = 61m). Most seeds handled for consumption (93%) were fully eaten but others were dropped intact (3%) or only partially eaten (4%), and germination was confirmed for both intact and partially-eaten dispersed seeds. Moreover, seeds dropped by cockatoos facilitated secondary seed dispersal by conspecifics and another three bird species. We found no evidence of other primary dispersal species for A. bidwillii, while the small, winged seeds of A. cunninghamii were just dispersed through barochory and anemochory. The seed weight of the three Araucaria species dispersed by zoochory is strongly related to the body mass of their main seed-dispersing parrot species. These results support a role for parrots as key dispersers of the three large-seeded Araucaria species around the world, and suggest that large seeds may have evolved–at least partially–as an adaptation that allows trees to attract parrots, satiate them, and benefit from their long-distance seed dispersal services.